Nitrogen release and loss, and kenaf response to controlled-release urea fertilizers applied to bris soils - Abdullah, Halimatul Sa'adiah (2012)
Kenaf has been identified to replace tobacco which is widely planted in Beach Ridges Interspersed with Swales (BRIS) soils area. Urea fertilizer had been used widely in agriculture as a major source of nitrogen (N). However, urea fertilizer can be easily leached. Therefore, control release urea (CRU) fertilizers are excellent alternatives for BRIS soil because they release nutrients slowly and plants are able to absorb without waste. The objectives of this study were to determine the nitrogen release, loss and kenaf response to control-released urea (CRU) fertilizers applied on BRIS soils. The specific objectives were to determine of the BRIS soils properties and characteristics of CRU fertilizers, to determine the mineralization of N and ammonia volatilization loss under laboratory condition, and the effect of CRU application on N uptake by kenaf grown on BRIS soil. The investigation consist of Study 1, Study 2, Study 3 using two BRIS soil series viz Rhu Tapai and Rudua. Both of soil series and were treated with four treatments viz Meister-20, Duration type-V, Uber-l O, and typical urea as a control. In Study 1, determination of the BRIS soil properties and characteristics of CRU fertilizers were conducted. In Study 2, determinations of mineralization of Nand ammonia volatilization loss under laboratory condition were conducted. In determination of mineralization of N, treated soil samples were analyzed for eight weeks. NH3-N volatilization was determined for two weeks. In Study 3, effect of CRU application on N uptake by kenaf grown on BRIS soils were conducted. BRIS soils which were mixed with 2 t/ha palm oil mill effluent, was filled into culverts measuring 24 x 55 em in diameter x height. Kenaf seed was sown at the center of the culvert. Two N rates were used in this study viz 300 and 600 kgN/ha. Determination of mineral N in treated soil was also being carried out monthly for five months. The culverts were arranged in a randomized complete block design. The effectiveness of treatments was determined by analyzing the plant height, yield, and availability of N in the plant tissues and replicated three times. Analysis of variance was used to analyze the data to detect significant differences. Treatments means were compared using Tukey at 5% level of significance. In laboratory condition, CRU released NH4-N, N03-N, and Urea-N lower than typical urea in eight weeks of experiment. CRU also released NH3-N volatilization lower than typical urea in two weeks of experiment. In field study, typical urea released NH4-N, N03-N, and Urea-N higher at early stage of experiment then decreased rapidly. However, CRU released NH4-N, N03-N, and Urea-N lower at early stage of experiment and maintain over five months. In terms of kenaf performances, the CRU gave significantly higher yield and N uptake. The results showed that the fertilization at rate of 300kg Nlha was enough to give the same results as 600kg N/ha and about 50% of fertilizer can be saved .. Therefore, the CRU fertilizers 'can increase the effectiveness of urea application for plant growth.